Analisis Tingkat Kematangan Layanan dan Produktivitas SDM Menggunakan COBIT 4.1 (Studi Kasus: UPT-TIK UPN “Veteran” Jawa Timur) - Clariza Risanti (Journal Of Information System And Artificial Intelligence, 2023)
UPT-TIK is a technical service unit at UPN "Veteran" East Java which has a service function in the field of Information and Communication Technology (ICT) to all work units, including lecturer staff, employees, students and services to the general public. The Covid-19 pandemic has caused many activities at UPN "Veteran" East Java to be switched online. To carry out activities online, assistance is needed from an information system that can process activities online. UPT-TIK as a technical service unit that serves in the field of Information and Communication Technology plays a large role in this matter to be able to provide services through information systems optimally. So it is important for UPT-TIK to be able to maximize the productivity and services of existing human resources. So in this study, measurement of the maturity level of services and productivity of human resources at UPT-TIK was carried out. The research was conducted by conducting a literature study, determining business goals, interviews, and analyzing and calculating the maturity level results with the framework used, namely COBIT 4.1.